1980
DOI: 10.1038/283264a0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of acetylcholinesterase appearance at neuromuscular junctions in vitro

Abstract: The appearance of acetylcholinesterase (AChE) at newly formed nerve-muscle synapses depends on synaptic transmission. Synapses form when cultures are grown in the presence of acetylcholine receptor antagonists, but AChE does not accumulate at these synapses. The important component of transmission seems to be muscle activity. Treatment with dibutyryl cyclic GMP mimics muscle activity, directly inducing synaptic AChE appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
85
1
1

Year Published

1982
1982
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(93 citation statements)
references
References 28 publications
6
85
1
1
Order By: Relevance
“…It has been suggested that, while clustering of AChRs at the nervemuscle contact does not depend on muscle activity, the loss of multi-endplate status and accumulation of AChE may depend on muscle activity (Giacobini et al, 1973;Lomo and Slater, 1978;Rubin et al, 1980;and review in Bennett, 1983). Development of organized neuromuscular junctions in the rat has also been considered to be linked to muscle activity (Lomo et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that, while clustering of AChRs at the nervemuscle contact does not depend on muscle activity, the loss of multi-endplate status and accumulation of AChE may depend on muscle activity (Giacobini et al, 1973;Lomo and Slater, 1978;Rubin et al, 1980;and review in Bennett, 1983). Development of organized neuromuscular junctions in the rat has also been considered to be linked to muscle activity (Lomo et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…La stimulation du muscle squelettique adulte provoque une augmentation très importante de la concentration en GMPc musculaire (Nestler et al, 1978). De même, l'addition de GMPc à des cultures de muscle mime les effets de l'activité sur l'AChE synaptique (Rubin et al, 1980 Fambrough, 1983 ;Sanes et Chiu, 1983 (1983,1984), Nitkin etal. (1983Nitkin etal.…”
Section: A) Propriétés Des Fibres Musculairesunclassified
“…Incompetent neurons, such as those of dorsal root ganglia and other noncholinergic neurons, are ineffective in this regard, thereby emphasizing the neural specificity of the triggering interaction (Cohen and Weldon, 1980;Role et al, 1985). The neural agent(s) that initiates these remarkable changes in AChR distribution has not yet been identified, but it is known that it can act in the absence of activation of AChRs, as well as in the absence of muscle and neuronal action potentials Rubin et al, 1980;Davey and Cohen, 1986). The response of the muscle cell to the triggering event includes a process of receptor redistribution whereby preexisting mobile AChRs in neighboring regions of the surface membrane aggregate along the path of neurite-muscle contact where they become immobilized Stya and Axelrod, 1984;Ziskind-Conhaim et al, 1984;Kidokoro et al, 1986).…”
mentioning
confidence: 99%